Respostas

2013-12-02T22:02:03-02:00
X-y=5
x=2y+1

agora vc vai substituir o x de cima

(2y+1)-y=5
1y-1y=5
0y=5
y=5

agora substitua o valor de y na 2 equção
x=2×5+1
x=10+1
x=11

×=11
y=5
1 5 1
  • Usuário do Brainly
2013-12-03T01:30:43-02:00
A)
x - y = 5
x = 2y + 1
----------
substitua:
(2y + 1) - y = 5
2y + 1 - y = 5
2y - y = 5 - 1
y = 4
--------------
substitua:
x - y = 5
x - (4) = 5
x - 4 = 5
x = 5 + 4
x = 9
-----------
S = { 9, 4 }

b)
x + y = 9
y = x - 5
---------
substitua:
x + (x - 5) = 9
x + x - 5 = 9
2x = 9 + 5
2x = 14
x = 14/2
x = 7
-----------
substitua:
y = x - 5
y = (7) - 5
y = 7 - 5
y = 2
-------------
S = { 7, 2 }